A trend analysis of breast cancer incidence in Sri Lanka, 2005-2019a - Saddharma Weerakoon; Malvige Amila Suranaga; Janaki Vidanapathirana; Upuli Perera (College of Community Physicians of Sri Lanka, 2022)
Introduction: Breast cancer is the commonest cancer among females globally as well as in Sri Lanka. There were 2.3 million women diagnosed with breast cancer and 684 996 deaths due to breast cancer globally in 2020.   Objective: To analyse the trends and patterns ofincidence ofbreast cancer in Sri Lanka between 2005 and 2019.   Methods: Cancer incidence data published in National Cancer Registry, Sri Lanka (NCR-SL) from 2005 to 2019 was analyzed. Age standardized rates (ASR), and age specific incidence rates were used to determine the trends of the breast cancer. Trend analysis of these two rates were performed using j oinpoint regression program and p<O. 05 was used to determine the statistical significance of the trends.   Results: ASRs of breast cancer among males and females in Sri Lanka have been increased gradually from 2005 to 2019. Female to male ratio for breast cancer incidence in 2019 was 3 5: 1. ASR of breast cancer among females was 18 .4 per 100 000 population in 2005, while it was 33 .5 per 100 000 population in 2019. The ASR of both females and males demonstrated an increasing trend and average annual percent changes (AAPC) were of 4.24 (95% CI: 3.4, 5.0) and 7. 72 (95% CI: 4.0, 11.6), respectively.   Conclusions & Recommendations: Current ASR of breast cancer is comparatively low in Sri Lanka, but the increasing trend is alarming. The trend has been influenced by the changes of incidence rates after the age of 65 years. It is time to implement evidence-based interventions to control breast cancer in Sri Lanka.